Systematic TOR1A non-c.907_909delGAG variant analysis in isolated dystonia and controls. (October 2016) - Zech, Michael; Jochim, Angela; Boesch, Sylvia; Weber, Sandrina; Meindl, Tobias; Peters, Annette; Gieger, Christian; Mueller, Joerg; Messner, Michael; Ceballos-Baumann, Andres; Poewe, Werner; Haslinger, Bernhard; et al.
Abstract: Background: An increasing number of rare, functionally relevant non-c.907_909delGAG (non-ΔGAG) variants in TOR1A have been recognized, associated with phenotypic expressions different from classic DYT1 childhood-onset generalized dystonia. Only recently, DYT1 genotype-phenotype correlations have been proposed, awaiting further elucidation in independent cohorts. Methods: We screened the entire coding sequence and the 5′-UTR region of TOR1A for rare non-ΔGAG sequence variants in a large series of 940 individuals with various forms of isolated dystonia as well as in 376 ancestry-matched controls. The frequency of rare, predicted deleterious non-ΔGAG TOR1A variants was assessed in the European sample of the Exome Aggregation Consortium (ExAC) dataset. Results: In the case cohort, we identified a rare 5′-UTR variant (c.-39G > T), a rare splice-region variant (c.445-8T > C), as well as one novel (p.Ile231Asn) and two rare (p.Ala163Val, p.Thr321Met) missense variants, each in a single patient with adult-onset focal/segmental isolated dystonia. Of these variants, only p.Thr321Met qualified as possibly disease-related according to variant interpretation criteria. One novel, predicted deleterious missense substitution (p.Asn208Ser) was detected in the control cohort. Among European ExAC individuals, the carrier rate of rare, predicted deleterious non-ΔGAG variants was 0.4%. Conclusions: Our study does not allow the establishment of genotype-specific clinical correlations for DYT1. Further large-scale genetic screening accompanied by comprehensive segregation and functional studies is required to conclusively define the contribution of TOR1A whole-gene variation to the pathogenesis of isolated dystonia. Highlights: Preliminary genotype-phenotype correlations have been proposed for DYT1. We identified 5 non-ΔGAG TOR1A variants in 940 dystonia cases. One non-ΔGAG TOR1A variant was present in 376 controls. The carrier rate of predicted damaging non-ΔGAG TOR1A variants at ExAC is 0.4%. The role of non-ΔGAG TOR1A variants in dystonia remains to be further elucidated.